Investigating the hydration of C3A in the combined presence of anhydrite and limestone using solid-state NMR, XRD and TG techniques. (16th May 2023) - Merlo, Valentino; Marchese, Leonardo; Gastaldi, Daniela; Boccaleri, Enrico; Canonico, Fulvio; Paul, Geo
Abstract: Diverse AFm phases are commonly found during the hydration of calcium sulfoaluminate (CSA), Portland (OPC), and calcium aluminate (CAC) cements. Due to the flexibility in their layered double hydroxide (LDH) structure, they are observed in variable single or multi-anion bearing forms, water contents and transient states. When multiple sulfate and carbonate anion sources, in variable compositions, are available during the hydration of cements, the identity, quantity, and stability of the formed AFm phases vary considerably. They may also precipitate as microcrystalline and/or amorphous phases, rendering their detection by X-ray powder diffraction (PXRD) difficult. In this study the AFm phases have been generated through the hydration of tricalcium aluminate (C3 A) in the presence of sulfate (anhydrite) and carbonate ions (limestone) in various compositions. A multi-technique approach involving solid-state nuclear magnetic resonance spectroscopy (ssNMR), thermogravimetric analysis/differential scanning calorimetry (TGA/DSC) and PXRD has been employed to govern the sequence of hydration reactions, the evolution, structure, and the stability of AFm phases at 1 and 28 days of C3 A hydration. The results show that the identity and quantity of AFm phases formed vary considerably according to the nature of the anion sources available during the hydration. Hydration products such as crystalline C3 AH6, ettringite and amorphous as well as crystalline/microcrystalline monoanionic AFm phases (monosulfate, monocarbonate, hydroxy-AFm) and bi-anionic phases (hemicarbonate and solid-solutions involving more anions) have been identified and quantified.